Virulensi beberapa Isolat Colletotrichum musae terhadap Buah Pisang dan Ketahanan Beberapa Buah Kultivar Pisang terhadap Colletotrichum musae - Toekidjo Martoredjo (Universitas Gadjah Mada, 1995)
Colletotrichum musae was isolated from banana cultivar of Ambon Hijau, Ambon Kuning, Emas, Gabu, Kepok, Kidang, Raja Gintung, Raja Sepet, Raja Temen, Raja Uter, Susu, and Tanduk. Virulency test showed that Raja Sepet, Raja Temen, and Susu C. musae isolates much more virulent than Tanduk isolate, while Ambon Kuning isolates its virulent is between two those groups. So Raja Sepet isolate is the highest virulent isolate and Tanduk isolate is the lowest virulent one. Resistancy test showed that Raja Temen, Ambon Hijau, and Raja Uter banana cultivars are much more resistant than Raja Gintung and Tanduk banana cultivars, while Raja Lumut, Kepok, Susu, Ambon Kuning, and Raja Uter banana cultivars their resistancy are between two those groups. So Ambon Hijau banana cultivar is the highest resistant banana cultivar and Tanduk banana cultivar is the lowest resistant one.